Control de Varroa destructor Oudemans en Apis mellifera L., con dos extractos vegetales - Verde Girbau, Carlos (2013)
The profitability of beekeeping is generating interest in solving the many questions inherent in this technique, the low Scientific Technical support, poor circulation and lack of status and of the institutions involved in one way or another I have motivated to give an alternative solution in the control varroasis, ectoparasite bound to generate significant losses today in the world of beekeeping, all this today is associated requirements in product free of contamination, this effect in the present work and taking the technical implementation of Thymol, organic product known by beekeepers for its efficiency in controlling Varroa destructor Oudemans, a trial was carried out by applying organic products, such as Huamansamana and oregano extracts macerated in alcohol, in three doses 2%, 5%, 8%, these products were applied in two different sectors, industry and sector Poloponta Sabinal, both in the District of Zapatero, Provincia de Lamas, San Martín region, used in both sectors 12 hives which then pass the initial test for this pest infestation, which exceeded the permissible limit is 3%. After the application of the extracts was determined a final proof of infestations in that treatment based Huamansamana 5% (T5), which was obtained the best result, in the doses Orégano 8% (T3) and 2% (T2), and reaffirmed the Thymol (Witness) as a product effective in controlling Varroa destructor O.